DELAY RED FLAG CONSTRUCTION COMPANY: CONTROL ANALYSIS WITH FOUR LEVER OF CONTROL - Notoatmodjo, Brigitta; Handoko, Jesica (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
Despite extensive research on construction delays, this persistent issue continues to challenge the global construction industry. This case study aims to enhance the theoretical and practical understanding of management control systems (MCS) in construction firms by identifying the primary causes of project delays and examining the MCS components involved. A qualitative case study was conducted at a national private construction company (Jakons) to identify delay factors and propose solutions by linking them to MCS. The study focused on two Jakons projects that experienced delays, with primary data collected through interviews with five key informants directly engaged in MCS for the projects. Analysis of the interviews revealed common delay causes related to the project owner, consultants, labor, and materials. These causes were then connected to MCS practices and assessed using the four Levers of Control (LoC) framework, including Belief, Boundary, Diagnostic, and Interactive control systems. The study identified areas for improvement in MCS related to communication management, coordination, competence, and risk management that impact schedule delays. These findings provide valuable guidance for construction practitioners in planning and managing projects and offer insights to reassess MCS strategies to mitigate delays and achieve timely project completion.